(untitled) (Journal of Engineering, 2024)
The study aimed to find the best amount of cellulose nanofibers to add to heat-cured denture base material to enhance its mechanical characteristics. Cellulose nanofibers (CNF) were added to the polymethyl methacrylate (PMMA) denture base in several weight percentages (0%, 0.5%, 1%, 1.5, and 2%). A probe sonicator was used to mix the monomer with the cellulose nanofibers for around 5 minutes. Impact strength, transverse strength, and shore D surface hardness were the three groups that were classified afterward according to the trials conducted. Descriptive statistics, including means, standard deviations, and bar chart visualisations, were utilised to analyse the data. The findings indicate that the mean values of impact strength and transverse strength measurements exhibited a significant increase in the 0.5% and 1% cellulose nanofiber reinforcement groups, as compared to the control group. However, no significant increase was observed in shore D hardness. Other percentages (1.5% and 2% by weight of CNF) either significantly or insignificantly decreased the mean value of the results. The findings suggest that the incorporation of cellulose nanofibers at concentrations of 0.5% and 1% improves the mechanical properties of a denture foundation.